Exchanging recipes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The cultivation of maize is a relatively recent introduction to the Sahelian countries, as a result of which most women have notinherited a traditional knowledge of how to process and prepare it. By contrast its preparation holds no secrets for...